Biology, gut content, and toxicity studies of spotted-green puffer fish collected from Sampadi, Kuching - Sarmila, Muthukrishnan (Universiti Malaysia Sarawak, UNIMAS, 2010)
The biology and toxicity of 104 samples were analyzed and 10 samples were used for gut content analysis. Samples of 104 fish with total lengths ranging from 9.90 cm to 17.30 cm were collected from Sampadi, Kuching using three layer gill nets in December, 2010. The physical appearances such as spots characteristic and colour of the body were observed by naked eyes and the numbers of dorsal, anal, and pectoral fin rays were counted using dissecting microscope. From the results, the standard length and body weight ranged from 7.60 cm to 13.00 cm and 40.66 g to 177.18 g respectively and shows significant difference in size between male and female. T.nigroviridis is omnivores which prey on invertebrates and leafs such as copepod, crustacean, gastropods, polychaete, small crabs and leafs. The gut content analysis supports the exogenous hypothesis in TTX accumulation through the diet. The anatomical distribution of toxicity level was tested by using mouse bioassays. Skins shows the higher toxicity score (155.80 ± 76.17) MU/g followed by eggs, gonad, liver, and muscles. Thin layer chromatography (TLC) was carried under two solvent systems. The Rf value are 0.77 and 0.22 respectively showing the existence of TTX in T. nigroviridis.